Belgium : 2009 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2010)
The 2009 Article IV Consultation highlights that the near-term outlook for Belgium is challenging, with real GDP expected to drop by about 3 percent in 2009 and a gradual recovery projected for 2010. The unemployment rate will continue to rise in 2010, and inflation pressures are expected to remain subdued. Uncertainty to the outlook is high but risks appear broadly balanced. The crisis will have a considerable downward impact on potential growth, in addition to that of demographic factors, in 2009-11.